Dynamics Of The Role Of Nahdlatul Ulama (NU) In The Development Of Islamic Educational Institutions In Bengkulu Selatan District - Ani AJ Jayanti (Universitas Islam Negeri Fatmawati Sukarno, 2022)
Based on NU's entry into the South Bengkulu region, there is no reason why NU education is not growing rapidly. Therefore, the author wants to study and further research NU education in South Bengkulu Regency so that it is easier for NU leaders and the government and society in general to evaluate existing NU organizations and NU education. The research method used is qualitative and this type of research is field research with a qualitative descriptive approach. The purpose of this method is to describe what it means in a critical analysis of NU's contribution to the development of Islamic educational institutions in the South Bengkulu region. It must be explained as it is in order to understand its meaning. The application of this research method requires supporting sciences such as sociology, education, history of Islamic culture, etc. The results of the study show that so far NU has not had a formal educational institution branded NU, because basically NU itself does not want a degree, the most important thing is for the good of the people. As for the existence of pesantren, there is no sign of NU because NU doesn't want to show it. Because with the existence of an ID NU educational institution, it creates divisions outside NU. Sometimes getting the NU label means that non-NU people can't enter, so with the general label, non-NU people can come and study, NU doesn't want symbols, so the individual amaliyah has a very important role as yasinan, in making taklim.